Edukasi Tentang Konsumsi Sayur Dan Buah Pada Anak Sekolah Di UPT SDN 060831 - Izmi Arisa Putri Lubis; Athira Demitri; Balqis Nurmauli Damanik; Intan Fadilah Hasanah; Juwita Diah Indriyani (STIKES Columbia Asia Medan, 2023)
This community service program aims to raise awareness and knowledge about the importance of consuming vegetables and fruits among school children at UPT SDN 060831. Through a series of educational activities including lectures, interactive discussions, and hands-on practices, the program strives to instill healthy eating habits in students. The approach employed involves enjoyable and participatory learning methods to ensure that students not only understand the nutritional benefits of vegetables and fruits but are also motivated to change their eating patterns. The results of this program show a significant increase in students' nutritional knowledge and positive changes in their vegetable and fruit consumption behavior. Additionally, this program is expected to have a long-term impact in creating a school environment that more strongly supports healthy eating habits.